Central Mandibular Nerve Sheath Myxoma - Narges Ghazi; jahanshah salehinejad; Shapoor Yaripour; Arash dehghan; Elham baradaran nasseri; Mehdi Shahabinejad (Mashhad University of Medical Sciences, 2018)
Nerve sheath myxoma has been described as a rare neural tumor arising from Schwann cells. It is observed most frequently in the central area of the face, neck and upper extremities. In the past the term neurothekeoma was used as synonym for nerve sheath myxoma but according to new reports, they are separate entities which can be confirmed by immunohistochemistry as in our case. Oral involvement of this tumor is extremely rare. Here, we present an unusual case of nerve sheath myxoma in the mandible of a 22-year old female patient. This case appears to be the first myxomatous variant which is centrally located in the mandible.